Kepemimpinan Kepala Sekolah dalam Mewujudkan Prestasi Sekolah - N. Etit Herawati (Universitas Muhammadiyah Kuningan, 2024)
The success of education in schools is largely determined by the success of the principal in managing the educational staff available at the school. The school principal is one component of education that has an influence on improving teacher performance. The principal, as the highest leader who is very influential and determines the progress of the school, must have administrative skills, have high commitment and be flexible in carrying out his duties. The urgency of this research is that school principals as managers are required to have adequate managerial skills. The aim of the research is to determine and describe the managerial abilities of school principals from the aspects of conceptual skills, human skills, technical skills in improving school achievement. The research method used in this research is descriptive with a qualitative approach. The results of the research show that: 1) The leadership of the principal at SD Negeri 1 Padarek, Kuningan District is at the capable criteria, this can be seen from the leadership of the principal as an educator, manager, administrator, supervisor, leader, innovator, and principal as a motivator. 2) School achievements at SDN 1 Padarek, Kuningan District, in terms of academic and non-academic achievements, have achieved good achievements at the local level.